2022 16th International Conference on Ubiquitous Information Management and Communication (IMCOM) 2022
DOI: 10.1109/imcom53663.2022.9721784
|View full text |Cite
|
Sign up to set email alerts
|

Brand Post Popularity on Social Media: A Systematic Literature Review

Abstract: Social media has now become an indispensable marketing tool. Much research has been done to understand what makes brands' social media posts popular by attracting Likes, Comments and/or Shares. The objective of this paper is to carry out a systematic literature review on brand post popularity on social media. Through a literature search on Scopus-the largest database of peer-reviewed literature, 19 relevant articles were identified. Facebook has been the most widely studied platform while only a handful of wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
(102 reference statements)
1
9
0
Order By: Relevance
“…Call to action in rebuttals also contributed to their virality. The marketing and consumer engagement literature has shown that social media posts that nudge consumers to act tend to become popular online [11]. Dovetailing the literature, this paper shows that a call to action is an important trait for not only marketing messages but also rumor rebuttals.…”
Section: Rumormentioning
confidence: 59%
See 4 more Smart Citations
“…Call to action in rebuttals also contributed to their virality. The marketing and consumer engagement literature has shown that social media posts that nudge consumers to act tend to become popular online [11]. Dovetailing the literature, this paper shows that a call to action is an important trait for not only marketing messages but also rumor rebuttals.…”
Section: Rumormentioning
confidence: 59%
“…Explicit calls to action could be important in rumor rebuttals to drive home their intended purpose. By encouraging users to actively participate in myth-busting efforts, they are more likely to go viral than rebuttals that do not include a call to action statement [11,18].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations